Investigasi Performa Turbin Angin Crossflow Dengan Simulasi Numerik 2D - Diniar Mungil Kurniawati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Wind turbine is a solution to harness of renewable energy because it requires wind as the main energy. Wind turbine work by extracting wind energy into electrical energy. Crossflow wind turbine is one of the wind turbines that are developed because it does not need wind direction to produce maximum efficiency. Crossflow wind turbines work with the concept of multiple interactions, namely in the first interaction the wind hits the first level of turbine blades, then the interaction of the two winds, the remainder of the first interaction enters the second level blades before leaving the wind turbine. In the design of crossflow wind turbine the diameter ratio and slope angle are important factors that influence to determine of performance in crossflow wind turbine. In this study varied the angle of slope 90 ° and variations in diameter ratio of 0.6 and 0.7. The study aimed to analyze the effect of diameter ratio and slope angle in performance of the crossflow wind turbine. This research was conducted with numerical simulation through 2D CFD modeling. The results showed that the best performance of crossflow wind turbine occurred at diameter ratio variation 0.7 in TSR 0.3 with the best CP value 0.34.